profile-img
Aparna Dash Asked a Question
October 25, 2020 4:35 pmpts 30 pts
tan A +sin A = m tan A - sin A = n 16 1. A m+n= 2 tan m - n = 2 sin A mn= tan A - sin A (m-n) (m+n) (m-n and and Now mn mn 2 (2 tan A) (2 sin A) tan A-sin A 16 tan? A sin A16 sin A tan A 3(sinx-cos x+6(sinx+ cos x+4 (sin" x+C 13
  • 2 Answer(s)
  • 1 Likes
  • 2 Comments
  • Shares
  • Priyanshu kumar Best Answer
    Follow the step....In your solution they skip 3 to 4 steps so confusion arises.
    • cropped585236217379778295.jpg
    Likes(1) Reply(0)
  • Priyanshu kumar thankyou
    Can you please send this question ?
    Likes(0) Reply(1)
    Aparna Dash
    here it is
    • cropped2051588401878196074.jpg